Robage BOT - Sushant Pawar; Kuldeep Rai; Rohitkumar Rai; Tejas Mestry (International Journal of Engineering and Management Research, 2023)
One of the biggest issues facing the entire globe today is waste management. Rapid population growth is a result of fast industrialisation, which also causes problems with waste management. It has been observed that there is a considerable likelihood that dumping light weight solid waste items may pollute public areas where the public congregates momentarily. There is no ideal method for keeping an eye on and maintaining these locations. It is possible to create a self-controlled robot application to solve these issues. Here machine can identify garbage and separate it into several categories, such as metallic and non-metallic waste.Implemented system uses IR sensors to detect garbage, metal proximity sensors to distinguish between metallic and non-metallic junk, and moisture sensors to further divide garbage into wet and dry waste. Here robot is controlled by an ESP32 microcontroller.